Vigilancia y privilegio periodístico en la era de las nuevas tecnologías de las telecomunicaciones bajo la Convención de Derechos Humanos y Libertades Fundamentales y la Constitución de la República de Polonia - Podkowik, Jan (2015)
The digital age has reconfigured the security services, especially the forms of mass surveillance aimed at preventing various threats to society. However, this scenario may become problematic from the perspective of protecting the freedom of the media and journalistic privilege. The author of this article offers an overview of the scope of the protection of the journalistic privilege pursuant to the European Convention for the Protection of Human Rights and Fundamental Freedoms, as well as its management in Poland from the developments prepared by its Constitutional Court.